2017
DOI: 10.1016/j.msea.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Study on the residual stress relaxation in girth-welded steel pipes under bending load using diffraction methods

Abstract: This research is dedicated to the experimental investigation of the residual stress relaxation in girthwelded pipes due to quasi-static bending loads. Ferritic-pearlitic steel pipes are welded with two passes, resulting in a characteristic residual stress state with high tensile residual stresses at the weld root. Four-point bending is applied to generate axial load stress causing changes in the residual stress state. These are determined both on the outer and inner surfaces of the pipes, as well as in the pip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…No stress relaxation for pulsating pressure loads was found as long as the maximum equivalent stress is below the cyclic yield strength. Hempel et al 32 investigated residual stress relaxation in welded steel pipes and concluded that the tensile load stress can generate residual stress relaxation depending on the magnitude and direction of the load as well as the level of residual stresses. Furthermore, these authors clarified also that equivalent von Mises stress identifies locations of plastic yielding and hence locations where residual stress relaxation can occur.…”
Section: State Of the Artmentioning
confidence: 99%
“…No stress relaxation for pulsating pressure loads was found as long as the maximum equivalent stress is below the cyclic yield strength. Hempel et al 32 investigated residual stress relaxation in welded steel pipes and concluded that the tensile load stress can generate residual stress relaxation depending on the magnitude and direction of the load as well as the level of residual stresses. Furthermore, these authors clarified also that equivalent von Mises stress identifies locations of plastic yielding and hence locations where residual stress relaxation can occur.…”
Section: State Of the Artmentioning
confidence: 99%
“…10(a). Furthermore, the axial tensile stresses on the inner surface are balanced by the axial compressive stresses on the FZ and HAZ of girth welding on the outer surface [18]. Therefore, axial bending deformation is produced through the pipe cross section.…”
Section: Structural Response In Case Amentioning
confidence: 99%
“…voids can be arose due to specific volume differences induced by precipitation, different thermal expansion or shrinkage upon heating or cooling the specimen. It has been known that nucleation, growth and coalescence of voids are deemed as the primary mechanism of ductile material fracture, in which voids growth is particularly important [12]. The initiation of crack at microscopic scale is a dynamic process, which results in difficulties on study of mechanism about deformation and cracking, these defects are known playing a fundamental role in the deformation of materials.…”
Section: Introductionmentioning
confidence: 99%